Assessment and condition monitoring of a concrete railway bridge in Kiruna, Sweden - Enochsson, Ola; Elfgren, Lennart; Olofsson, Thomas; Täljsten, Björn; Töyrä, Björn; Kronborg, Anders; Paulsson, Björn (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2006)
A two-span railway concrete trough bridge over Luossajokk in Kiruna in northern Sweden has been studied. The owner wanted to increase the axle loads from 250 to 300 kN in order to reduce freight costs for iron ore. Examples are given of methods used and results obtained from the assessment where bending, shear and fatigue were studied. Material properties, loads and load carrying capacity were evaluated using deterministic and probabilistic methods. It was shown that the bridge could carry the higher loads with a safety index β > 4.7 for reasonable assumptions of the load distributions. A measurement system was installed to check the actual level of critical strains and the worst positions of the train. Results are also given from a condition monitoring program 2001-2006, launched to periodically check the development of strains with time. Godkänd; 2006; Bibliografisk uppgift: Abstract pp 887-888. Full paper P-332, 8 p, on attached CD; 20061111 (ysko)